Fine Needle Aspiration Biopsy Mempunyai Peranan Penting dan Akurasi Tinggi Sebagai Metode Diagnostik Preoperatif Tumor Tulang - Norahmawat, Eviana (Fakultas Kedokteran Universitas Brawijaya, 2009)
ABSTRACTFine Needle Aspiration Biopsy (FNAB) technique is gaining increasing popularity in the diagnosis ofmusculoskeletal lesions because it offers some advantages such as rapid , easy , with minimal complications,but its applicability in diagnosis of bone tumors however has some limitations. This research was aimed toexplore the roles of FNAB and its accuracy as the preoperative diagnostic method compared tohistopathology examination from open biopsy or operation as a gold standard. Research design wasdescriptive study and diagnostic test from cases of bone tumors which were aspirated over a period of threeyears in Anatomic Pathology Laboratory of Saiful Anwar Hospital Malang. The data was collected with crosssectional method. Of the 106 patients who were subjected to FNAB, 22 cases were diagnosed as benignbone tumor,49 were primary malignant bone tumor,24 were metastatic malignant bone tumor,1 cases wassuspicious malignant tumor, 5 cases were non neoplastic lesions, and 5 cases were inadequate/ inconclusivefor diagnosis. Of the 16 cases which was analized with diagnostic test, sensitivity of FNAB as preoperativediagnostic method was 100 %, specificity was 90,91%, positive predictive value was 83,33 % and negativepredictive values was 100 % . Overall, diagnostic accuracy of FNAB was 93,75 %.It can be concluded that